2021
DOI: 10.1108/he-11-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

University students' knowledge about and attitudes toward e-cigarette use and factors influencing students' e-cigarette use

Abstract: PurposeThis study aims to investigate university students' knowledge about and attitudes toward e-cigarette (EC) use. It will also examine whether students' EC use is associated with knowledge about and attitudes toward EC use. The study also aims to analyze the determinants of students' use of ECs. The effects of gender, smoking behavior and friends' and family members' smoking behaviors on students' use of ECs were analyzed.Design/methodology/approachCompleted questionnaire surveys were received from 1,362 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…In this regard, a cross-sectional study in Pakistan among post-graduate medical trainees showed that there was a significant correlation between being a current smoker and possessing a higher amount of knowledge regarding e-cigarettes [26]. However, our results contradicted the ones found by Chudech and Janmaimool (2021) in Thailand wherein they found that the university students who were using e-cigarettes reported less knowledge, but a higher positive attitude toward e-cigarettes than those who were not using them. This contradiction might be due to the reason that university students are more mature than school students and have enough knowledge about the harmful effects of e-cigarettes.…”
Section: Discussioncontrasting
confidence: 94%
“…In this regard, a cross-sectional study in Pakistan among post-graduate medical trainees showed that there was a significant correlation between being a current smoker and possessing a higher amount of knowledge regarding e-cigarettes [26]. However, our results contradicted the ones found by Chudech and Janmaimool (2021) in Thailand wherein they found that the university students who were using e-cigarettes reported less knowledge, but a higher positive attitude toward e-cigarettes than those who were not using them. This contradiction might be due to the reason that university students are more mature than school students and have enough knowledge about the harmful effects of e-cigarettes.…”
Section: Discussioncontrasting
confidence: 94%
“…The results also revealed that male students, students who had also smoked tobacco, and students with friends who smoked tobacco were more likely to use e-cigarettes (33). Therefore, the use of e-cigarettes among students can significantly increase the overall use of e-cigarettes.…”
Section: Discussionmentioning
confidence: 90%